Analisis Pembangunan Desa Berbasis Perencanaan Di Desa Tang Kecamatan Bokat Kabupaten Buol - Muhammad Nasir Hasan Dg Marumu; Ramlawati Ramlawati; Irawati Ahmad (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
Village development aims to improve the welfare of the village community and the quality of human life as well as poverty alleviation through basic fulfillment, development of village facilities and infrastructure, development of local economic potential, and sustainable use of natural resources and the environment. Tang Village, Bokat District, Buol Regency as one of the government units under the government is required to compile a development planning document, namely the Village Medium-Term Development Plan (RPJM Desa) and the Village Annual Development Plan or the so-called Village Government Work Plan (RKP Desa) for village development. Considering this is a responsibility, it must be carried out by the Tang Village Government. The involvement or participation of the community is an absolute requirement in the process of preparing the Village Government work plan (RKP Desa). This involvement is intended so that the community can make a positive contribution to village development planning. The research aims to be analyzed to determine the planning-based village development in Tang Village, Bokat District, Buol Regency. This type of research uses a descriptive analysis method with a qualitative approach so that the case studies obtained in this study can be compared with the experiences of other researchers. The research method used is the descriptive analysis method with a qualitative approach using a frequency table and then interpreted based on categories according to the data obtained in the field (primary data) which is then descriptively measured using a Likert Scale. The conclusion in this study is that planning-based village development in Tang Village, Bokat District, Buol Regency reaches the Very Good category.